2009
DOI: 10.1128/aem.02649-08
|View full text |Cite
|
Sign up to set email alerts
|

Coculture Fermentations ofBifidobacteriumSpecies andBacteroides thetaiotaomicronReveal a Mechanistic Insight into the Prebiotic Effect of Inulin-Type Fructans

Abstract: Four bifidobacteria, each representing a cluster of strains with specific inulin-type-fructan degradation capacities, were grown in coculture fermentations with Bacteroides thetaiotaomicron LMG 11262, a strain able to metabolize both oligofructose and inulin. In a medium for colon bacteria with inulin as the sole added energy source, the ability of the bifidobacteria to compete for this substrate reflected phenotypical variation. Bifidobacterium breve Yakult, a strain that was not able to degrade oligofructose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 45 publications
6
85
2
Order By: Relevance
“…This is in contrast to coculture studies with B. thetaiotaomicron and various Bifidobacterium strains (33). In these cases, B. thetaiotaomicron does release short-chain oligofructose molecules into the medium following extracellular inulin degradation, which different bifidobacterial species have varying abilities to use (33). Analysis of the activity of fractionated R. inulinivorans cells to degrade fructans did not indicate significant extracellular activity, although the cell pellets and sonicated material were active.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…This is in contrast to coculture studies with B. thetaiotaomicron and various Bifidobacterium strains (33). In these cases, B. thetaiotaomicron does release short-chain oligofructose molecules into the medium following extracellular inulin degradation, which different bifidobacterial species have varying abilities to use (33). Analysis of the activity of fractionated R. inulinivorans cells to degrade fructans did not indicate significant extracellular activity, although the cell pellets and sonicated material were active.…”
Section: Discussioncontrasting
confidence: 43%
“…longum that uses fructose and scFOS was unable to grow in coculture with R. inulinivorans A2-194, indicating that there was no extracellular accumulation of monomeric units during degradation of inulin by R. inulinivorans. This is in contrast to coculture studies with B. thetaiotaomicron and various Bifidobacterium strains (33). In these cases, B. thetaiotaomicron does release short-chain oligofructose molecules into the medium following extracellular inulin degradation, which different bifidobacterial species have varying abilities to use (33).…”
Section: Discussioncontrasting
confidence: 41%
“…While B. breve is not known to be able to grow on mucin or HMOs, host-derived mono/oligosaccharides may become available through hydrolytic activities of other (bifido)bacteria present in the gut (e.g., B. bifidum and B. longum subsp. infantis), allowing B. breve strains to utilize such liberated carbohydrates through cross-feeding activities (74)(75)(76).…”
Section: Figmentioning
confidence: 99%
“…Some species of the genus Bacteroides, including Bacteroides thetaiotaomicron, are known to be decomposers in the colon by fermenting carbohydrates and catabolizing polysaccharides (hemicellulose and xylan) (Falony et al, 2009;Flint, 2006;Salyers, 1995;Van der Meulen et al, 2006). Novel strains of members of the genus Bacteroides from human faeces and intestinal organs have been identified using cultureindependent techniques based on 16S rRNA gene sequence analysis (Dore et al, 1998; Eckburg et al, 2005; Gill et al, 2006;Hayashi et al, 2003;Li et al, 2009;Palmer et al, 2007) and several novel species have recently been identified and characterized (Bakir et al, 2006a, b, c;Chassard et al, 2008; Hayashi et al, 2007;Kitahara et al, 2005;Robert et al, 2007;Song et al, 2004).…”
mentioning
confidence: 99%